2016
DOI: 10.3390/ijms17101758
|View full text |Cite
|
Sign up to set email alerts
|

Stage-Wise Identification and Analysis of miRNA from Root-Knot Nematode Meloidogyne incognita

Abstract: In this study, we investigated global changes in miRNAs of Meloidogyne incognita throughout its life cycle. Small RNA sequencing resulted in approximately 62, 38, 38, 35, and 39 Mb reads in the egg, J2, J3, J4, and female stages, respectively. Overall, we identified 2724 known and 383 novel miRNAs (read count > 10) from all stages, of which 169 known and 13 novel miRNA were common to all the five stages. Among the stage-specific miRNAs, miR-286 was highly expressed in eggs, miR-2401 in J2, miR-8 and miR-187 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…The digital expression profile of these miRNAs showed differential expression across five disease development stages suggesting their probable role during nematode parasitism. For example, conserved miRNAs including miR-100_3, miR-58_1 and lin-4 showed a notable differential expression at different stages in concordance to the previous studies [ 25 27 ]. The target prediction of RKN miRNAs provided limited data due to the lack of 3’UTRs annotation of some RKN genes.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The digital expression profile of these miRNAs showed differential expression across five disease development stages suggesting their probable role during nematode parasitism. For example, conserved miRNAs including miR-100_3, miR-58_1 and lin-4 showed a notable differential expression at different stages in concordance to the previous studies [ 25 27 ]. The target prediction of RKN miRNAs provided limited data due to the lack of 3’UTRs annotation of some RKN genes.…”
Section: Discussionsupporting
confidence: 90%
“…Recently, cancer associated gender specific miRNAs were identified among human males and females [ 24 ]. Additionally, recent studies on identification and characterization of RKN miRNAs suggested their role in nematode development and parasitism [ 25 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…A putative mechanism to establish massive gene repression is the activation of small RNA (sRNA) pathways that repress gene expression at the transcriptional or translational level (Ruiz-Ferrer and Voinnet, 2009). In line with this, the roles of different microRNAs (miRNAs) on the plant-RKN interaction have been addressed recently Díaz-Manzano et al, 2016a, 2018Kaur et al, 2017;Medina et al, 2017;Subramanian et al, 2016;Zhang et al, 2016;Zhao et al, 2015). However, little is known about the regulatory role of other types of siRNA in this interaction.…”
Section: Introductionmentioning
confidence: 99%
“…After the report on the whole genome sequence of M. incognita in the year 2008, research has focused on a search for stage-specific genomic or molecular markers which can be developed into potential targets to control this plant-parasitic nematode [ 1 , 7 ]. Currently, there is no available resource on general and/or stage-specific metabolites from M. incognita .…”
Section: Introductionmentioning
confidence: 99%